PEMBINAAN NILAI - NILAI ADAT BASANDI SYARAK, SYARAK BASANDI KITABULLAH OLEH NINIK MAMAK TERHADAP ANAK KEMENAKAN DI KENAGARIAN SITUJUAH GADANG KEC LIMO NAGARI KAB.LIMA PULUH KOTA - Yohanis, Yohanis (Ensiklopedia of Journal, 2020)
This Jurnal collaborated of couching about Adat Basandi Syarak, syarak Basandi Kitabullah which is conducted by ninik mamak, The aim is fostering nephew’s character to better that apporiate with philosophy of Adat Basandi Syarak, syarak Basandi Kitabullah , it related through (a) the couching has done by ninik mamak toward rephew and (b). factor’s is become abstacle of founding by. Jurnal examine point research which the informan is determind by purposive sampling, it is determine them by consideration it give maximum data which is collected by interview and study documentation it has done by teehnique analysis of data which is qualitative technique analysis the result o the research shows about founding which counducted by ninik mamak in dialog with the nephews become model for them.